POTENSI RHIZOBAKTERI DALAM MENDUKUNG PERTUMBUHAN STEK BATANG SINGKONG (Manihot esculenta Crantz) [The Potential of Rhizobacteria in Supporting the Growth of Cassava (Manihot esculenta Crantz ) Stem Cuttings] - Nugroho, Agung Adi; Agustiyani, Dwi; Sutisna, Entis; Mulyani, Nani; Dewi, Tirta Kumala; Nditasari, Achirul; Antonius, Sarjiya; Purwaningsih, Sri (Berita Biologi, 2023)
Cassava (Manihot esculenta Crantz) is an important food plant in Indonesia, particularly as a carbohydrate source. We require a plan to increase production and quality. The use of Plant Growth Promoting Rhizobacteria (PGPR) in organic fertilizers is one option. The aim of this study is to isolate, characterize, and evaluate potential microbial candidates for cassava greenhouse growth. K solubilizing, P solubilizing, N fixing, IAA production, protease production, ACC-deaminase, and siderophore production were investigated in 15 tuber root rhizobacteria isolates. The bacterial isolates' ability to grow cassava stem cuttings was then assessed. The rhizobacterial inoculation treatments in this study included fifteen single isolates, a combination of isolates, and controls. With three replications, the experimental design was completely randomized. Five P-solubilizing bacterial isolates (PK AL.2.2, PK LAS 4A.4, PK 4.1, PK Al.2.6, PK Kbm 6.1), two protease-producing isolates (Pro LAS 4B.6 and Pro LAS 5A.3), and one IAA-producing isolate (TSB LAS 1A.6) increased wet plant weight by 20-41% as compared to controls. The results of molecular identification of the six excellent isolates were Burkholderia sp. (PK AL.2.2), Paenarthrobacter nicotinovorans (Pro LAS 4B.6), Burkholderia territorii (PK 4.1), Burkholderia cenocepacia (Pro LAS 5A.3), Burkholderia territorii (PK LAS 4A.4), and Kocuria rhizophila (TSB LAS 1A.6).